Dzieje krakowskiego domu przy ul. Krupniczej 26 (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
HISTORY OF THE PALACE AT 26 KRUPNICZA STREET IN CRACOWThe author presents the history of the palace and its origins. At the turn of the 15th century there was a large house on this site, with a pottery inside. Later, in the 17th century, there was a suburban guesthouse there, then replaced by a little wooden manor surrounded by a garden. According the Cracow City Map of 1820, made by Ignacy Enderle, it was the estate No 127, district IX, and it belonged to the Solecki family. The building and its courtyard were 150 and the garden 525 Viennese fathoms (ancient area measures). In 1826 the estate was a property of the Grzybowski family. After several years it belonged to a Cracow merchant Mateusz Rogowski. The Rogowski’s house was destroyed by a fire in 1850 — the most severe fire of Cracow. In 1854 another house in brick was built on this site by Rogowski. It was a one-storey house designed by Dr Ignacy Hercok. One of the greatest Polish 19th-century poets and painters, Stanislaw Wyspiański, was born in that house on 15 January 1869. In 1873 the house was remodelled to form a residence of Professor J. Szujski. He was an outstanding Polish historian and playwright, the Rector of the Jagiellonian University and a co-founder of the Academy of Arts and Letters in Cracow. The residence was designed by architect Antoni Łuszczkiewicz. The palace housed a magnificent scientific library and works of art. Szujski played an important role in Cracow’s scientific, cultural and political life, so the house was always full of guests. Szujski lived there for 10 years. He died prematurely at the age of 47, in 1883. In the 1880s the house got number 26, the same as it has toady. In 1896 the real property was passed to countess Róża Tarnowska, born Branicka. She turned the palace into a tenement house. In 1932 it was bought by an outstanding Polish painter Józef Mehoffer, the Rector of the Academy of Fine Arts in Cracow. He had the palace reconstructed and furnished with many works of art, including his own works — paintings, cartoons for polychromy, drawings and stained-glass. The palace was called te ‘Under the Cones Palace’ and became the Mehoffer family residence. The residence in the city centre, with a big Mehoffer family coat-of-arms over the gate, surrounded by a large garden, became the artist’s home, being at the same time a sort of museum and a place for artists’ meetings. Mehoffer lived there for 10 years. He died in 1946. Forty years later, on the Mehoffer family initiative, ‘The Józef Mehoffer’s House’ was established here as a branch of the National Museum in Cracow.